The redemptive self : stories Americans live by - McAdams, Dan P. (Oxford University Press, 2006)
This book identifies and explores a particular story about life - a narrative identity. At the centre of this life story is the concept of redemption as the deliverance from suffering to a better world. Adults with high psychological measures showing a caring and productive approach to life think of their lives as as narratives of redemption.